O-GlcNAcase Expression is Sensitive to Changes in O-GlcNAc Homeostasis - Zhang, Zhen; Tan, Ee Phie; VandenHull, Nicole J.; Peterson, Kenneth R.; Slawson, Chad (Frontiers in Endocrinology, 2014)
O-linked N-acetylglucosamine (O-GlcNAc) is a post-translational modification involving an attachment of a single β-N-acetylglucosamine moiety to serine or threonine residues in nuclear and cytoplasmic proteins. Cellular O-GlcNAc levels are regulated by two enzymes: O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), which add and remove the modification respectively. The levels of O-GlcNAc can rapidly change in response to fluctuations in the extracellular environment; however, O-GlcNAcylation returns to a baseline level quickly after stimulus removal. This process termed O-GlcNAc homeostasis appears to be critical to the regulation of many cellular functions including cell cycle progress, stress response, and gene transcription. Disruptions in O-GlcNAc homeostasis are proposed to lead to the development of diseases such as cancer, diabetes, and Alzheimer’s disease. O-GlcNAc homeostasis is correlated with the expression of OGT and OGA. We reason that alterations in O-GlcNAc levels affect OGA and OGT transcription. We treated several human cell lines with Thiamet-G (TMG, an OGA inhibitor) to increase overall O-GlcNAc levels resulting in decreased OGT protein expression and increased OGA protein expression. OGT transcript levels slightly declined with TMG treatment, but OGA transcript levels were significantly increased. Pretreating cells with protein translation inhibitor cycloheximide (CHX) did not stabilize OGT or OGA protein expression in the presence of TMG; nor did TMG stabilize OGT and OGA mRNA levels when cells were treated with RNA transcription inhibitor actinomycin D (AMD). Finally, we performed RNA Polymerase II chromatin immunoprecipitation (ChIP) at the OGA promoter and found RNA Pol II occupancy at the transcription start site (TSS) was lower after prolonged TMG treatment. Together, these data suggest that OGA transcription was sensitive to changes in O-GlcNAc homeostasis and was potentially regulated by O-GlcNAc.